A crime so monstrous - Skinner, E. Benjamin (Free Press, 2008)
Includes bibliographical references and index; There are more slaves in the world today than at any time in history. In this account of contemporary slavery, journalist Skinner travels around the globe to personally tell stories that need to be told--and heard. With years of reporting in such places as Haiti, Sudan, India, Eastern Europe, The Netherlands, and, yes, even suburban America, Skinner has produced a moving reportage on one of the great evils of our time. After spending four years infiltrating trafficking networks and slave sales on five continents, he tells the story of individuals who live in slavery, those who have escaped from bondage, those who own or traffic in slaves, and the mixed political motives of those who seek to combat the crime. Their stories are heartbreaking but, in the midst of tragedy, readers discover a quiet dignity that leads some slaves to resist and aspire to freedom.--From publisher description